A follow up model for patients with atrophic chronic gastritis and intestinal metaplasia. Issue 2 (27th January 2004) - Dinis-Ribeiro, M; Lopes, C; da Costa-Pereira, A; Guilherme, M; Barbosa, J; Lomba-Viana, H; Silva, R; Moreira-Dias, L
Abstract : Aim: To devise a follow up model for patients with gastric cancer associated lesions, such as atrophic chronic gastritis (ACG) and intestinal metaplasia (IM). Methods: Cohort study of 144 patients, followed for a minimum of one year, in whom at least two upper gastrointestinal endoscopic biopsies in flat gastric mucosa provided a diagnosis of ACG, IM, or low grade dysplasia (LGD). Results: Of those diagnosed with ACG at first endoscopic biopsy (entry biopsy), 12% progressed to LGD in outcome biopsy, as did 8% of those with type I IM, 38% with type II or III IM, and 32% with LGD. Type of IM at entry independently predicted progression to LGD and cancer. Type II and III IM had a higher rate of progression to LGD than type I IM, which showed an indolent behaviour similar to ACG. Patients with type II or III IM were at higher risk for development of dysplasia, and 7% of patients with type III IM at first biopsy progressed to high grade dysplasia (HGD), whereas no cases of ACG or type I/II IM progressed to HGD during the first three years. Conclusion: Patients with ACG or IM could possibly be allocated to different management schedules, based on differences in rate and proportion of progression to LGD or HGD. Less intensive follow up (two/three yearly with "serological evaluation" (pepsinogen)) may suit those with ACG or type I IM. Patients with type III IM may benefit from six to 12 monthly improved endoscopic examination (magnification chromoendoscopy).